The Effectiveness of Pricing Strategy on Purchasing Decisions for Bookkeeping and Chasiers Paccounting Applications by Panemu - I Wayan Langit Baliage Wayan; Albari (Jurnal Economic Resource, 2023)
This research was conducted to determine whether there is an effectiveness of pricing strategy on purchasing decisions for bookkeeping applications and cashier PAccounting by PT Panemu Solusi Industri. This study used a descriptive qualitative approach with direct observation methods and interviews by companies. The conclusion in this study is that companies apply several different Paccounting pricing strategies, including discount pricing strategies, freemium pricing strategies, premium pricing strategies, and psychological pricing strategies. Each strategy used has a different purpose, where the discount pricing strategy is expected to make consumers choose the highest price package, then the freemium pricing strategy focuses on attracting potential users with a trial period at no cost, while the premium pricing strategy offers consumers with a full-featured application, and the psychological pricing strategy aims to make potential customers think that the product is not expensive. The results showed that the four strategies had a positive impact on consumer interest seen from the increase in sales for 3 years.